Optimization of πT Hybrid Structure of 110 kV Power Grid - Zhiyong SHI; Guomin WANG; Qi GENG; Yuan ZHANG; Tianhua WANG (发电技术)
There are some operational problems of the πT hybrid structure, such as large workload of operation and maintenance, poor flexibility and scalability, which can not meet the increasing demand for power supply reliability. In this paper, the optimization scheme of the πT hybrid structure connection structure was put forward, and the technical and economic demonstration of the optimization scheme was carried out. The concrete alteration scheme of πT mode to chain π connection mode was studied, and the networking principle of 110 kV power grid was established, which can direct the implementation and landing of the optimization of the 110 kV power grid with πT hybrid structure.